Stakeholder perceptions of performance audit credibility. Issue 6 (18th September 2016) - Funnell, Warwick; Wade, Margaret; Jupe, Robert
Abstract : This paper examines the credibility of performance audit at the micro-level of practice using the general framework of Birnbaum and Stegner's theory of source credibility in which credibility is dependent upon perceptions of the independence of the auditors, their technical competence and the usefulness of audit findings. It reports the results of a field study of a performance audit by the Australian National Audit Office conducted in a major government department. The paper establishes that problems of auditor independence, technical competence and perceived audit usefulness continue to limit the credibility of performance auditing.